Time‐restricted feeding during the inactive phase abolishes the daily rhythm in mitochondrial respiration in rat skeletal muscle. Issue 2 (15th January 2022) - de Goede, Paul; Wüst, Rob C. I.; Schomakers, Bauke V.; Denis, Simone; Vaz, Frédéric M.; Pras‐Raves, Mia L.; van Weeghel, Michel; Yi, Chun‐Xia; Kalsbeek, Andries; Houtkooper, Riekelt H.
Abstract: Shift‐workers show an increased incidence of type 2 diabetes mellitus (T2DM). A possible mechanism is the disruption of the circadian timing of glucose homeostasis. Skeletal muscle mitochondrial function is modulated by the molecular clock. We used time‐restricted feeding (TRF) during the inactive phase to investigate how mistimed feeding affects muscle mitochondrial metabolism. Rats on an ad libitum (AL) diet were compared to those that could eat only during the light (inactive) or dark (active) phase. Mitochondrial respiration, metabolic gene expressions, and metabolite concentrations were determined in the soleus muscle. Rats on AL feeding or dark‐fed TRF showed a clear daily rhythm in muscle mitochondrial respiration. This rhythm in mitochondrial oxidative phosphorylation capacity was abolished in light‐fed TRF animals and overall 24h respiration was lower. The expression of several genes involved in mitochondrial biogenesis and the fission/fusion machinery was altered in light‐fed animals. Metabolomics analysis indicated that light‐fed animals had lost rhythmic levels of α‐ketoglutarate and citric acid. Contrastingly, lipidomics showed that light‐fed animals abundantly gained rhythmicity in levels of triglycerides. Furthermore, while the RER shifted entirely with the food intake in the light‐fed animals, many measured metabolic parameters (e.g., activity and mitochondrial respiration) did not strictly align with the shifted timing of food intake, resulting in a mismatch between expected metabolic supply/demand (as dictated by the circadian timing system and light/dark‐cycle) and the actual metabolic supply/demand (as dictated by the timing of food intake). These data suggest that shift‐work impairs mitochondrial metabolism and causes metabolic inflexibility, which can predispose to T2DM.